Insight into the effects of H2SO4 and HNO3 acidification processes on the properties of coal as an enhanced adsorbent for ciprofloxacin residuals: Steric and energetic studies - Al-Labadi, Ibrahim G.; Shemy, Marwa H.; Ghidan, Alaa Y.; Allam, Ahmed A.; Kálmán, Horváth M.; Ajarem, Jamaan S.; Luo, Jianmin; Wang, Chuanyi; Abukhadra, Mostafa R. (Frontiers in Chemistry, 2023)
A sub-bituminous natural coal sample (R.C) was treated with sulfuric acid (S.C) and nitric acid (N.C) as modified products and enhanced adsorbents for obtaining ciprofloxacin (CFX) antibiotic residuals from water. The characterization studied demonstrates enhancement in the surface area and the incorporation of new active oxygenated, sulfur-bearing, and nitrogen-bearing chemical groups into the structure of coal samples. This was reflected in the adsorption capacities that were enhanced from 164.08 mg/g (R.C) to 489.2 mg/g and 518.5 mg/g for N.C and S.C, respectively. The impact of the acid modification processes was evaluated based on the energetic and steric properties of their adsorption systems considering the parameters of the advanced monolayer equilibrium model with one energy site. The determined occupied active sites’ density of R.C (46.32–61.44 mg/g), N.C (168.7–364.9 mg/g), and S.C (159.2–249.9 mg/g) reflects an increase in the quantities of active centers after the acid treatment processes, especially with HNO3. The higher efficiencies of the active sites of S.C to adsorb more CFX molecules (n = 2.08–2.31) than N.C (n = 1.41–2.16) illustrate its higher adsorption capacity. The energetic investigation [adsorption (˂40 kJ/mol) and Gaussian (˂8 kJ/mol) energies] suggested adsorption of CFX by N.C and S.C mainly by physical processes such as van der Waals forces, hydrogen bonding, dipole bonding, and π–π interactions. Moreover, the determined thermodynamic functions including entropy, internal energy, and free enthalpy reflect the spontaneous and endothermic uptake of CFX on the surfaces of N.C and S.C.